2019
DOI: 10.4209/aaqr.2019.08.0422
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Air Toxics Characteristics and Inhalation Health Risk Assessment of a Metropolitan Industrial Complex

Abstract: Air toxics, also well-known as hazardous air pollutants (HAPs), have significant health effects on human health and are of great concern. This paper studied a number of hazardous air pollutants in an industrial and metropolitan complex area in order to determine their ambient abundance and potential health impacts. The target pollutants in this study are benzene, formaldehyde, 1,3-butadiene, arsenic, 2,3,7,8-TCDD, and diesel particulate matter (DPM). A cancer risk assessment was conducted to determine the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Inhalation of As cement dust caused 0.007 × 10 -4 times greater likelihood of developing cancer (Addo et al, 2016). It was estimated that the 95% cancer risk due to exposure to As from industrial emission in Xiaogang, Taiwan is 0.04 × 10 -4 (Tsai et al, 2019). The previous study found less of As cancer risk due to the concentration exposure is lower and below the permissible exposure limit.…”
Section: Incremental Lifetime Cancer Risk (Ilcr)mentioning
confidence: 98%
See 1 more Smart Citation
“…Inhalation of As cement dust caused 0.007 × 10 -4 times greater likelihood of developing cancer (Addo et al, 2016). It was estimated that the 95% cancer risk due to exposure to As from industrial emission in Xiaogang, Taiwan is 0.04 × 10 -4 (Tsai et al, 2019). The previous study found less of As cancer risk due to the concentration exposure is lower and below the permissible exposure limit.…”
Section: Incremental Lifetime Cancer Risk (Ilcr)mentioning
confidence: 98%
“…Studies on Cr (VI) exposure have found high cancer risk among respondents (Fang et al, 2013;Othman et al, 2016;Sulong et al, 2017;Xu et al, 2019). Industrial contributes to 68.7% of arsenic emission into the environment with 0.04 × 10 -4 times of cancer risk (Tsai et al, 2019). Controlling the exposure factors of crystalline Si dust can profoundly reduce the ILCR among workers (Yeheyis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The absolute carcinogenic risk is usually estimated by multiplying the actual VOC concentration and its carcinogenic risk factor [48]. However, to ensure comparability among different emission sources, carcinogenicity was calculated for each emission source on a relative basis (Eq.…”
Section: Rcrmentioning
confidence: 99%
“…The absolute carcinogenic risk is usually estimated by multiplying the actual VOC concentration and its carcinogenic risk factor [47]. However, to ensure comparability among different emission sources, carcinogenicity was calculated for each emission source on a relative basis (Eq.…”
Section: 5relative Carcinogenic Risk (Rcr)mentioning
confidence: 99%